Fungsi Teater Rakyat Ubrug Bagi Masyarakat Banten - Nur Seha; Anitawati Bachtiar; Adek Dwi Oktaviantina; Rukmini Rukmini; Sehabudin Sehabudin (ATAVISME, 2014)
The purpose of this research is to describe the functions of the ubrug folk theater for Bantenese people. This study uses function theory and cultural studies. The data resources for the article is Mang Cantel’s Ubrug folk theater because it still often accepts the offer to perform on stage in wedding events in the area around Serang and Pandeglang. The method used in this research is a descriptive qualitative method. Meanwhile, the data collecting techniques are recording, interviewing, observing, making a transcription, and translating. The result of this research shows that ubrug folk theater has several functions for Bantenese people. The first function of ubrug is as a preservation media for Bantenese languages which are Serang Javanese and Banten Sundanese. Moreover, ubrug has become the media in moral education, media in a publicizing government program such as family planning (KB), and media of entertainment. Key Words: folk theater; function; ubrug Abstrak: Penelitian ini bertujuan mendeskripsikan fungsi teater rakyat ubrug bagi masyarakat Banten. Teori yang digunakan adalah teori fungsi dan kajian budaya. Sumber data penelitian ini adalah teater rakyat ubrug Mang Cantel karena ubrug Mang Cantel masih sering menerima tawaran pentas pada acara-acara hajatan di daerah sekitar Serang dan Pandeglang. Metode yang digunakan adalah metode deskriptif kualitatif. Pengumpulan data dilakukan dengan teknik perekaman, wawancara, pengamatan, transkripsi, dan terjemahan. Penelitian ini menghasilkan temuan bahwa teater rakyat ubrug memiliki beberapa fungsi bagi masyarakat Banten. Ubrug berfungsi sebagai media pemertahanan bahasa Jawa Serang dan Sunda Banten. Bahasa yang digunakan tersebut menjadi ruh pertunjukan sehingga dapat menjadi alat untuk mempertahankan bahasa dan budaya Banten. Selain itu, ubrug dapat menjadi media penanaman pendidikan moral, media informasi program pemerintah seperti Keluarga Berencana (KB), dan sebagai media hiburan